Interspecific association characteristics of Alternanthera philoxeroides-invaded communities and their latitudinal variations - Hao Wu; Hao Wu; Hao Wu; Sijin Dong; Sijin Dong; Meipeng Yu; Yuxin Liu; Benqiang Rao (Frontiers in Ecology and Evolution)
Biological invasions can lead to changes in the interspecific association and coexistence patterns of plant species; however, the differences in the interspecific association characteristics of invaded plant communities in heterogeneous habitats and their variations along latitudinal gradients remain unclear. Here, we established 40 terrestrial plots and 40 aquatic plots invaded by the amphibious invasive species Alternanthera philoxeroides (Mart.) Griseb. within the range of 21–37°N in China to explore the interspecific associations and association intensities of A. philoxeroides-invaded plant communities and their latitudinal trends. We found that there was a significantly positive interspecific association in the overall terrestrial communities, with A. philoxeroides having a strong association with many accompanying species. However, there was a nonsignificant negative interspecific association in the overall aquatic communities. The ratio of species pairs with positive/negative associations (PNR) in terrestrial communities dramatically decreased at higher latitudes. The values of the Jaccard index (JA), Ochiai index (OI), and Dice index (DI) which represent the interspecific association intensity in terrestrial communities, were extremely significantly greater than those in aquatic communities. The association intensity between terrestrial accompanying species significantly decreased with increasing latitude, and the association intensity between aquatic accompanying species varied weakly along the latitudinal gradient. Our study revealed that A. philoxeroides invasion aggravated interspecific competition among accompanying species in terrestrial plant communities in higher latitude regions, whereas the aquatic A. philoxeroides-invaded communities presented more mutualistic relationships to resist abiotic stress in higher latitude regions.